Online video revolution : how to reinvent and market your business using online video - Cecil, John. (New York : Palgrave Macmillan, 2012)
"The Internet is changing. Once a text based medium, it's now transitioning into a video based one. Simply put, marketing to your customers online using traditional techniques no longer works. Why video? It has the power to engage your customers and prompt a response. It can increase the time they stay on your site, influence what they buy, and feed their desire to trust you. This book will teach you how to properly utilize video to help bring your product to life and increase your conversions. Online video expert, John Cecil, provides a guide to successfully incorporating video into your marketing strategy and explains why it's essential in today's market. With the constant flow of information on the Internet, it's vital that you attain the complete attention of your consumer, and video can make this happen. It's been proven that online video will help turn web site visitors into buyers, increasing success and profits. This book details how video technology can be useful to you and outlines tools that can create online visibility and sustainability. Cecil provides techniques for producing and distributing video, maintaining a strategic online video marketing plan, and ultimately creating a greater return on your video investment. The author's approach to video marketing has already been successful for companies such as Canon, eHarmony, Capitol Records, and Experian. Video marketing needs to be a critical piece of a successful online strategy, and this book will teach you not only how to get started, but how your video project can pay for itself with increased ROI." -- Publisher's description.
Machine generated contents note: 1.Lights, Camera, Action! Text Goes to Video-Based Content -- 2.Video in the Media Mix: Where It's Been and Where It's Going -- 3.Participate in the Video Revolution -- 4.Creating Video: Top Considerations for Production Success -- 5.Return on Investment (ROI) -- 6.Delivery -- 7.Video Production -- 8.Video SEO---The Science of Getting Seen -- 9.Make Your Videos Social -- 10.Taking Your Video to the Bank.
Includes bibliographical references (p. [193]-202) and index.
Keywords: Internet advertising; Internet marketing; Internet videos; Internet advertising; Internet marketing; Internet videos